PJMHS 2022
DOI: 10.53350/pjmhs221651450
|View full text |Cite
|
Sign up to set email alerts
|

Pericardial Effusionin Patients Admitted in Emergency Department: Frequency and Causes

Abstract: Objective:A study of pericardial effusions in individuals with dyspnea was conducted to evaluate the prevalence and aetiology. Study Design:Prospective/Observational Study Place and Duration: Multicenteric study conducted at DHQ Hospital Bagh AJK/ Federal Govt. Polyclinic Hospital Islamabad and DHQ Teaching Hospital Gujranwala Medical College, Gujranwala. Duration was six months from 1st Oct 2021 to 31st March 2022. Methods:There were 135 patients of both genders had ages 18-75 years were presented in this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
1
0
0
Order By: Relevance
“…The patients belonged to the age group of 1 to 7 having mean age 45.23±7.52 years, we observed that the majority of the patients belonged to the male gender. The frequency of pericardial effusion in our study was 18 (15%), similar frequency has been reported by a study 18 which showed that 17% patients had pericardial effusion, and another study reported the prevalence of pericardial effusion 19.3% 19 .…”
Section: Discussionsupporting
confidence: 91%
“…The patients belonged to the age group of 1 to 7 having mean age 45.23±7.52 years, we observed that the majority of the patients belonged to the male gender. The frequency of pericardial effusion in our study was 18 (15%), similar frequency has been reported by a study 18 which showed that 17% patients had pericardial effusion, and another study reported the prevalence of pericardial effusion 19.3% 19 .…”
Section: Discussionsupporting
confidence: 91%